Nanoagregados baseados em ciclodextrinas em associação com a tetraciclina: caracterização fisico-química e avaliação antimicrobiana - Henrique Franca Diniz Oliveira (2007)
Molecular self-assembling has been shown to be an efficient method to produce structures of few hundreds of nanometers in size. The supramolecular compounds made from (R)-cyclodextrin:tetracycline in aqueous solution were evaluated. The physicochemical interactions between â-cyclodextrin:tetracycline were characterized by dynamic light scattering (DLS), isothermal titration calorimetry (ITC), X-ray diffraction (XD), infraredspectroscopy (FTIR), thermogravimetric analyses (TG), differential scanning calorimetry (DSC), and nuclear magnetic resonance (NMR). The supra-molecular interaction with A. actinomycetemcomitans and P. gingivalis in solution and in association with polymericnanospheres were determined. Using the characterization techniques, it was demonstrated that the formation of inclusion complex takes place at a 1:1 (R)-CD:TC molar ratio and, increasing (R)-CD concentration, supramolecular spontaneous aggregation occurred. The resultingcomplexes showed different physicochemical properties, nanometric size and improved antimicrobial activity. The 2:1 (R)-CD:TC showed significantly higher antimicrobial activity in nsolution (p<0.05). Among the other compounds, 4:1 was the most effective against P.gingivalis (inhibition zone = 41.67±1.4mm, MIC 0.25ìg/mL, p<0.05). Polymeric nanospheres were then manufactured using these nanoassemblies. The nanospheres showed controlled TC release for 10 days, and concentrations above minimum inhibitory concentrations of tested bacteria.